Use of Anakinra in steroid dependent recurrent pericarditis: a case report and review of literature - Vinay Kumar Thallapally; Sonia Gupta; Sai Giridhar Gundepalli; Joseph Nahas (Greater Baltimore Medical Center, 2021)
Non-steroidal anti-inflammatory drugs and colchicine are the cornerstone treatment for recurrent pericarditis. Corticosteroids are frequently used in patients with recurrent episodes of pericarditis. In patients with corticosteroid dependent and corticosteroid-resistant pericarditis, several steroid-sparing options like azathioprine, intravenous immunoglobulin (IVIG), and anakinra are being recently tried. In this article, we present the case of a 44-year-old male with recurrent pericarditis, who was successfully treated with anakinra. Abbreviations: Non-steroidal anti-inflammatory drugs, NSAIDS; Aspirin, ASA; Erythrocyte sedimentation rate, ESR; Serum Protein Electrophoresis, SPEP; Magnetic Resonance Imaging, MRI; C-Reactive Protein, CRP; Aspartate Aminotransferase, AST; Alanine Aminotransferase, ALT; Idiopathic recurrent pericarditis, IRP; Intravenous Immunoglobulin, IVIG.